The concept of corporate strategy - Andrews, Kenneth R. (Homewood, Illinois : R. D. Irwin, 1980)
The substance of this book is the subject matter of the field of professional study usually called business policy. The concept of strategy originated in professional schools of management. Its format has traditionally included complex cases, continually renewed, which present as far as practicable the total situation of a company.
Includes bibliographical references and index.
ne 12/07/2018
Loans
Keywords: Business planning